Notes on professional liability in psychotherapy - Scapati, F.; Greco, O.; Catanesi, R. (Medicina e Morale, 1988)
The current psychiatric context is characterised by a growing demand for psychological help and/or treatment; the increased demand has consequently led to a proportional expansion of the offer, which has led to the uncontrolled proliferation of psychotherapies and psychotherapists who have progressively extended their field of intervention well beyond the psychopathological disorder in the strict sense of the term, also targeting persons whose aim is not to 'normalise' their functions but to 'optimise' their performance.